Effect of yoga protocol in primary snoring: A pilot study - Jojan J Jerone; Ashok Patil; Savita S Angadi; Amal S Chandran (Wolters Kluwer Medknow Publications, 2023)
Introduction: Snoring is a highly prevalent condition characterized as "audible vibrations of the upper airway during sleep respirations." The currently available treatment modalities are costly and are associated with various complications. Methods: After obtaining ethical clearance and CTRI registration, twenty patients with primary snoring were recruited into the study group to follow a yoga protocol for 30 days. Participants were assessed on the baseline, 15th, and 30th days. The subjective parameters and objective parameters were assessed using Snoring Symptom Inventory (SSI) questionnaire and Snore lab mobile application respectively. Self-reported habitual snoring, a partner to provide the snoring report, turbinate hypertrophy grade I and II, mild deviated nasal septum, Body Mass Index <35 kg/m2, and age group 20-80 years were included. Patients with obstructive sleep apnea (OSA) and undergoing treatment for snoring or OSA, case of chronic rhinitis, three or more alcoholic drinks per day, conditions likely to affect OSA physiology were excluded. SSI questionnaire and snore score, percentage and time, and sleeping time were assessed using Friedman and Paired t-test. Results: Out of the 25 questions in the SSI questionnaire, 13 showed significant results. Highly significant improvement was seen in the snore score, time, and percentage. Significant changes were seen in the parameter neck circumference (P < 0.05) before and after the treatment. Conclusion: It can be concluded that yoga protocol is cost-effective, easy to administer, and effective nonpharmacological treatment in the management of primary snoring.